Effect of positive surgical margins at radical prostatectomy on cancer‐specific mortality in high/very high‐risk prostate cancer patients with Gleason Grade Group 4–5. Issue 3 (6th November 2022) - Panunzio, Andrea; Sorce, Gabriele; Hoeh, Benedikt; Hohenhorst, Lukas; Tappero, Stefano; Nimer, Nancy; Rajwa, Pawel; Tian, Zhe; Terrone, Carlo; Chun, Felix K. H.; Briganti, Alberto; Saad, Fred; et al.
Abstract: Background: The effect of positive surgical margins (PSM) on cancer specific mortality (CSM) in high/very high‐risk (HR/VHR) prostate cancer (PCa) with aggressive Gleason Grade Group (GGG) is unknown. We tested PSM effect on CSM in this setting, in addition to testing of radiotherapy (RT) benefit in PSM patients. Methods: We relied on Surveillance, Epidemiology, and End Results database (2010–2015), focusing on HR/VHR patients with exclusive GGG 4–5 at radical prostatectomy (RP). Kaplan–Meier plots and multivariable Cox regression models tested the relationship between PSM and CSM. Moreover, the effect of RT on CSM was explored in PSM patients. Results: Of 3383 HR/VHR patients, 15.1% ( n  = 511) exhibited PSM. Patients with PSM harbored higher rates of GGG 5 (60.1% vs. 50.9%, p  < 0.001), pathologic tumor stage T3a (69.1% vs. 45.2%, p  < 0.001) and lymph node involvement (14.1% vs. 9.4%, p  < 0.001), relative to patients without PSM. PSM rates decreased over time (2010–2015) from 16.0% to 13.6%. Seven‐year CSM‐free survival rates were 91.6% versus 95.7% in patients with and without PSM, respectively. In multivariable Cox regression models, PSM was an independent predictor of CSM (hazard ratio = 1.6, p  = 0.040) even after adjustment for age, prostate specific antigen, pathologic tumor stage and lymph node status. Finally, in PSM patients, RT delivery did not reduce CSM in either univariable or multivariable Cox regression models. Conclusions: In HR/VHR PCa patients with exclusive GGG 4–5, PSM at RP adversely affect survival. Moreover, RT has no protective effect on CSM. In consequence, lowest possible PSM rates are crucial in such patients.